From literal meaning to veracity in two hundred milliseconds - Martin, Clara D.; Garcia, Xavier; Breton, Audrey; Thierry, Guillaume; Costa, Albert (Frontiers in Human Neuroscience, 2014)
Do the integration of semantic information and that of world knowledge occur simultaneously or in sequence during sentence processing? To address this question, we investigated event-related brain potentials elicited by the critical word of English sentences in three conditions: (1) correct; (2) semantic violation; (3) world knowledge violation (semantically correct but factually incorrect). Critically, we opted for low constraint sentence contexts (i.e., whilst being semantically congruent with the sentence context, critical words had low cloze probability). The processing of semantic violations differed from that of correct sentences as early as the P2 time-window. In the N400 time-window, the processing of semantic and world knowledge violations both differed significantly from that of correct sentences and differed significantly from one another. Overall, our results show that the brain needs approximately 200 ms more to detect a world knowledge violation than a semantic one.